Laser ablation in titanium implants followed by biomimetic hydroxyapatite coating: Histomorphometric study in rabbits - Faeda, Rafael Silveira; Spin-Neto, Rubens [UNESP]; Marcantonio, Elcio; Guastaldi, Antonio Carlos [UNESP]; Marcantonio, Elcio [UNESP] (Wiley-Blackwell, 2012)
Titanium surface texture and chemistry modification successfully improves the host response and consequently the bone-to-implant contact surrounding dental implants. The aim of the present study was to investigate, using histomorphometrical-analysis, the effects of titanium surface modification by laser-ablation (Nd:YAG) followed by thin chemical deposition of HA. Forty-eight rabbits received one implant by tibiae of AS-machined (MS), laser-modified (LMS), or biomimetic hydroxyapatite-coated (HA) surface. Bone-to-implant contact (BIC) and bone area (BBT) were evaluated after 4, 8, and 12 weeks, at cortical and cancellous regions. Average BIC in the cortical region was higher (P < 0.001) on the LMS and HA implants for all periods, with no differences between LMS and HA. For the cancellous area, the LMS and HA implants showed higher (P < 0.01) BIC than MS at the initial periods. The LMS and HA showed similar values in the cortical region, but a tendency of higher values for HA in the cancellous region was observed in all periods. For the BBT, the differences were found only between HA and MS after 4 weeks in the cortical region (P < 0.05), and after 12 weeks in the cancellous area (P < 0.05). Our results showed that HA biomimetic coating preceded by laser treatment induced the contact osteogenesis and allowed the formation of a more stable boneimplant interface, even in earlier periods. Microsc. Res. Tech., 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: titanium implants; surface modification; hydroxyapatite; laser